Scenario-based teaching in teaching algebra in gifted education (Journal of Gifted Education and Creativity, 2025)
The purpose of this research is to investigate the effect of the scenario-based learning method in 6th and 7th grade Algebra teaching on the success of gifted and nongifted students in skill-based questions and their opinions about teaching. It is thought that learning with scenarios in the field of algebra will increase students' self-confidence in mathematics lessons and will help break down the prejudice they may have against skill-based questions. This research was conducted with seven gifted students and 58 non-gifted students. The model of the research is a mixed method in which qualitative and quantitative data are used together. According to the findings obtained from the research, there was a significant difference in favor of the posttest of the experimental group nongifted students in the course taught with the scenario-based learning method in algebra teaching, there was no significant difference in the pretest and posttest results in the control group taught by applying current teaching methods, and the results of the experimental and control groups were significantly different. It was observed that the posttest averages differed significantly in favor of the experimental group, while there was an increase in the total scores and achievement-based scores of gifted students in favor of the posttest. When the opinions of the experimental group students were examined, it was revealed that they were more effective in the lessons taught using scenario-based learning methods, they achieved permanent learning, their anxiety decreased compared to the current teaching, and they stated that they had fun.